Financial Cycles : Early Warning Indicators of Banking Crises? - Chen, Sally; Svirydzenka, Katsiaryna (Washington, D.C. : International Monetary Fund, 2021)
Can the upturns and downturns in financial variables serve as early warning indicators of banking crises? Using data from 59 advanced and emerging economies, we show that financial overheating can be detected in real time. Equity prices and output gap are the best leading indicators in advanced markets; in emerging markets, these are equity and property prices and credit gap. Moreover, aggregating this information flags financial crisis many years before the crisis. Lastly, we find that the length of financial cycles is of medium-term frequency, calling into question the longer frequency widely used in the estimation of countercyclical capital buffers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Fluctuations; Cycles; Foreign Exchange; Informal Economy; Underground Econom